Summary of threats for river dolphins in South America: Past, present and future - Trujillo, Fernando (2010)
In the early eighties a great concern about the future of river dolphins led the Cetacean Specialist Group of the IUCN Species Survival Commission to concentrate their efforts on strategy to deal with those concerns. In 1986, the Workshop on Biology and Conservation of the Platanistoid Dolphins was the first step to asses issues related with threats and recommendations for the survival of river dolphins in the entire world (Perrin et al. 1989). This meeting encouraged some researchers in South America to start long term river projects related to river dolphins, especially in Brazil and Colombia. For almost ten years some important contributions about the distribution, biology and identification of threats were made. During these years some documents were published. These documents were and are currently the lead information to all researchers involved in research, conservation and educational projects. These documents are the 1994-1998 Action Plan for the Conservation of Cetaceans (Reeves & Leatherwood 1994), International Whaling Commission Scientific Committee Report 2000, and the 2002-2010 Conservation Action Plan the World’s Cetaceans (Reeves et al. 2003).